Keys to deciphering the global geopolitical reality. Critical study of technological supremacy and its effects - Fraguas de Pablo, Rafael (Razón y fe, 2019)
Critical Geopolitics studies the connection between territory and power. Energy, automotion and computer science are today coveted by the United States and the great powers, Russia and China. They also fight for the control of the energetic subsoil and the increasingly militarized extra-atmospheric space. The nuclear arsenals have the capacity to remove the earth from its orbit. Technology is the weapon of the weapons in dispute. In the midst of the fray, financial capital, hostile to the democratic state, tries to appropriate it. It applies it without control to work and to a speculation that generates destructive crises that only benefit it: 26 people possess more capital than 8,000 million inhabitants of the Planet. The Science of Critical Geopolitics investigates the causes and verifies the effects of the processes that mock our world.